The Holy Spirit and Other Spirits in Asia: Discernment of Spirits in Non-Christian Religions - Cheong Weng Kit (Sekolah Tinggi Teologi Satyabhakti, Malang)
Malaysia is an ethnically diverse and religiously pluralistic nation. Within its population Christians number 9.2% while the remainder is comprised of Muslims (61.3%), Buddhists (19.8%), Hindus (6.3%), and other religions (3.4%) such as Confucianism, Taoism, folk/traditional/animistic religions, and others (Department of Statistics Malaysia, 2010). It is thus not surprising that any non-Christian to Christian encounter should implicate followers of Jesus, who are trying to understand whether non-Christians may be following the right path towards truth and also whether the spirits they worship are in any biblical sense the Spirit of truth of which Jesus speaks (Jn. 14:17; 15:26; 16:13) or that of another spirit. If interreligious relationships can be understood in this context, then the task of discerning the spirits, whether it is the Holy Spirit or “other” spirits at work, is of great importance. Biblically, all Christians are called to discern the spirits (1 Jn. 4:1-3) of those at work in this world as well as the truth or error that may be perpetuated behind these spirits.